2020
DOI: 10.3390/cells9020302
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Activity Induces Paracrine Signaling and Triggers Axonal Regrowth after Injury in Microfluidic Lab-On-Chip Devices

Abstract: Peripheral nerve injuries, including motor neuron axonal injury, often lead to functional impairments. Current therapies are mostly limited to surgical intervention after lesion, yet these interventions have limited success in restoring functionality. Current activity-based therapies after axonal injuries are based on trial-error approaches in which the details of the underlying cellular and molecular processes are largely unknown. Here we show the effects of the modulation of both neuronal and muscular activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 85 publications
2
24
0
Order By: Relevance
“…Consistent with previous works [23, 3335], we showed that increasing neuronal activity on DRG sensory neurons enhanced axonal growth in non-inhibitory in vitro and in vivo peripheral injury models. Additionally, and still accordingly to previous studies [36], we also demonstrated these effects in embryonic cortical cells in vitro, highlighting the presence of similar mechanisms among different neuronal types.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous works [23, 3335], we showed that increasing neuronal activity on DRG sensory neurons enhanced axonal growth in non-inhibitory in vitro and in vivo peripheral injury models. Additionally, and still accordingly to previous studies [36], we also demonstrated these effects in embryonic cortical cells in vitro, highlighting the presence of similar mechanisms among different neuronal types.…”
Section: Discussionsupporting
confidence: 93%
“…The design used for microfluidic devices was a modification of a previously published device(Taylor et al, 2005; Sala-Jarque et al, 2020). The resulting device consists in 4 receptacles of 7mm diameter, connected in pairs by a longitudinal compartment (cell body and axonal compartments) which are in turn interconnected by 100 microchannels (10μm x 10μm x 900μm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The designs used for microfluidic devices were modifications of previously published devices (Sala-Jarque et al 2020 ; Taylor et al 2005 ). One of the devices consists in 4 reservoirs of 7 mm diameter, connected in pairs by a longitudinal compartment (cell body and axonal compartments) which are in turn interconnected by 100 microchannels (10 μm × 10 μm × 900 μm).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, microfluidic vacuum aspiration followed by introducing air bubbles within the axonal compartment resulted in features linked to acute axonal degeneration, delayed bulb formation, and impairment of axonal mitochondrial transport [ 63 ]. A recent study used these techniques to mimic the role of myotubular contractility on axonal regeneration, where axons from motor neurons co-cultured with myotubes were injured using fluidic aspiration along with bubble introduction [ 64 ].…”
Section: Transection Injury Modelsmentioning
confidence: 99%